PEMBELAJARAN BAHASA INGGRIS BAGI SISWA USIA 15-18 TAHUN DESA KWALA BEGUMIT MELALUI METODE TOTAL PHYSICAL RESPONSE (TPR) - Maitri Ramadhani; Sayful Bahri (Jurnal Pengabdian Kepada Masyarakat, 2022)
Learning English has been carried out for a long time and has been included in the education curriculum in Indonesia. In its development, now English is the only compulsory foreign language subject that is taught starting from Junior High School to Senior High School. For about 6 years of learning English, students generally still cannot speak English orally with the assumption that their English learning is only focused on winning the written test which only refers to the grammatical / grammatical aspects. Meanwhile, his communication skills are not trained. Students are worried about mistakes they will make when they want to speak English due to grammar rules that have become the main focus of learning English at schools. By using the Total Physical Response Method, the community service officer tries to help students learn English. The results shown during the teaching and learning activities were quite encouraging. students can confidently speak English orally and do not show their boredom. The level of stress experienced by students in conventional methods is not visible when using this TPR method which is proven by their activeness in role playing. The TPR method is effective and can be applied as a learning method in English where community service partners are located.